A little ignorance is a dangerous thing: engaging with exogenous knowledge not adduced by the parties. Issue 3 (2nd July 2016) - Edmond, Gary; Hamer, David; Cunliffe, Emma
ABSTRACT: Using a recent trial and appeal in Canada as an example, this essay reviews our conventional reticence to allowing judges to draw the attention of counsel to issues that might influence the assessment of forensic science evidence in criminal proceedings. We question the institutional commitment to judicial non-intervention and suggest that on many occasions judicial passivity or quiescence (rather than impartiality) threatens the fundamental goals of fairness and factual rectitude. The essay explores the scope and rationale for judicial engagement with exogenous knowledge within the confines of adversarialism.